Debating Feminism on Instagram: A Critical Discourse Analysis of @LasIgualadas in Colombia - Veloso da Silva, Admilson; Cuesta López, Ana María (Information & Media, 2023)
The first organized feminist movement in Colombia demanded the right for women to vote in 1954 and, despite its progressist agendas and decades of work, it still tends to be distorted by traditional media representation. With social media, these activists can reach the audience directly, disseminate information, and dispute narratives. Hence, this study addresses the question: how are the discourses about feminism constructed on Instagram in Colombia? Based on netnography and critical discourse analysis, the paper analyzes the discussions on publications and comments on the most popular feminist Instagram account in Colombia, @LasIgualadas. The results indicate that the platform usage could help create a less stereotypical perspective on the movement while informing society on its agendas and raising awareness about rights violations. However, the debate on @LasIgualadas is still predominantly carried out by women (80.5%), and some topics, such as abortion and LGBTQI+ rights, are distorted or deviated from by some Instagram users’ comments.
Keywords: Instagram; Feminism; Colombia; Social Media; Critical Discourse Analysis; Netnography